Behavioural repertory of juveniles of the freshwater crab Poppiana dentata (Randall 1840) under laboratory conditions. Issue 1 (2nd January 2022) - Singh, Delezia S.; Alkins-Koo, Mary; Rostant, Luke V.; Mohammed, Azad
Abstract : The behavioural repertory for Poppiana dentata has not been previously reported in literature. Therefore, this study aimed to describe the repertory of behaviours for juvenile P. dentata, under laboratory conditions. An ethogram was used to categorize activities into seven main behavioural acts; foraging, eating, grooming, locomotion, quiescence (inactive), prolonged agonism and non-agonistic contact. Juvenile daily behaviour (n = 12) were continuously recorded over 72 hr and the time durations for each behavioural act were determined from viewing video footage (n = 864 hr). Activities over 24 hr were derived from percent daily proportions of each behavioural act. Overall, juvenile crabs spent most of their time foraging (54.8%) and resting (quiescence; 25.4%), while they performed eating (11.1%), grooming (5.3%), locomotion (2.6%) and displayed agonism (0.8%) to a lesser extent. Diurnal differences between light and dark phases were significant for foraging, quiescence and eating ( P < 0.05). Time spent on grooming, locomotion and prolonged agonism were higher in the light phase versus the dark but these photoperiodic variations were not significant ( P > 0.05). High occurrences of non-agonistic contact were similarly observed for light (101 events) and dark (93 events) phases, reflecting a gregarious nature for the juvenile stage of P. dentata . This behavioural repertory represents the first ethological description reported for the species.